E-LEARNING DI GAME EDUKASI ONLINE UNTUK ANAK-ANAK - Nia Karniawati; G M Rani (Jurnal Teknologi Informasi dan Pendidikan, 2020)
This study aims to identify e-learning as a branding of kids educational online games. Descriptive method was used to present a complete overview regarding the situation related to variables examined. The results of this research are to recognize the development of branding and the benefit provided by e-learning in the application of educational games for kids. Discussing the product branding of e-learning games for kids was conducted in this research.